ANALISIS PERBANDINGAN BIAYA KONSTRUKSI MATERIAL BAJA DAN MATERIAL BETON PADA PEMBANGUNAN MALL PELAYANAN PUBLIK DI JALAN ELTARI KECAMATAN ALOK KABUPATEN SIKKA - Yohana Ema Muda; Margaretha Yuneta; Triapriono Kaidu (SIARTEK - Jurnal Teknik Sipil dan Arsitektur, 2025)
Reinforced concrete plays a scurecal role in the construction industry. The primary components of concrete are cement,fine aggregate (sand),coarse aggregate (gravel), and water,with the potential addition of chemical additives to enhance its uality.On the other hand, steel stuctures are excellent for earthuake resistance due to the material’s superior strength and ductility compared to otherstructural materials like concrete.The purpose of this research is to determine the budget for reinforced concrete structures, compare the costs between steel and reinforced concrete construction, and evaluate the cost difference between steel and reinforced concrete sctructures. The public service mall project data indicates that a steel structure was used.The results of the cost comparison showed that steel sctructures are more economical. The cost for the existing steel constuction was 1.390.830.035,73, while the cost for concrete concstruction was 1.572.927.091,00 , resulting in a cost difference of 182.092.055,27